2008
DOI: 10.1021/jp8011156
|View full text |Cite
|
Sign up to set email alerts
|

Well-Ordered V2O5(001) Thin Films on Au(111): Growth and Thermal Stability

Abstract: Vanadium oxide thin films were grown on Au(111) by the oxidation of vapor-deposited V layers with 50 mbar of oxygen. The structure, composition, and thermal stability of the films have been investigated with scanning tunneling microscopy, low energy electron diffraction, photoemission spectroscopy, near-edge X-ray absorption fine structure, and temperature-programmed desorption. Well-ordered V2O5(001) thin films containing very few point defects have been obtained. Although the films have the tendency to grow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 66 publications
3
70
0
1
Order By: Relevance
“…2a). This binding energy agrees well with results previously obtained for a V 2 O 5 (001) film grown on a Au(111) crystal [64].…”
Section: Structural Characterization Of Vanadia Supported On Ceo 2 (111)supporting
confidence: 91%
See 1 more Smart Citation
“…2a). This binding energy agrees well with results previously obtained for a V 2 O 5 (001) film grown on a Au(111) crystal [64].…”
Section: Structural Characterization Of Vanadia Supported On Ceo 2 (111)supporting
confidence: 91%
“…3a. Based on C-H stretching vibrations observed in the IR spectrum (not shown) and comparison to similar IR spectra for methanol adsorption on partially reduced V 2 O 3 (001) thin films [64] , this peak is assigned to the C-O stretch of methoxy bound to vanadia, although there also may be a contribution to the peak intensity from vanadyl groups that remain on the surface and have only slightly differing frequencies (see Fig. 3a).…”
Section: 2mentioning
confidence: 90%
“…The peak position is in between the expected O1s peak of V 2 O 5 at about 530.0 eV (Mendialdua et al, 1995;Guimond et al, 2008;Zou et al, 2009) and the reported O1s positions of Al 2 O 3 , which are typically in the range 531-533 eV (Hinnen et al, 1994;van den Brand et al, 2004;Snijders et al, 2005). For the V-Al-C-N samples discussed here, the O1s and V2p spectra are similar (see Fig.…”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 74%
“…V 2 O 5 is a well-known oxidizing agent, and oxygen vacancies in V 2 O 5 are easily induced [ 12,[33][34][35][36] via annealing [ 35,36 ] and environmental exposure. [ 12,22 ] The reduction of V 5+ to lower oxidation states has been correlated with a decrease in the work function of V 2 O 5 fi lms, [ 22 ] which would represent an extraction barrier for holes from the solar cell.…”
Section: Introductionmentioning
confidence: 99%